Variability in double brooding of the great tit (Parus major) across polluted and resource-poor area - Wijayathunge Arachchige, Lasanthi Kanthika (My University, 2025)
Environmental changes such as climate change and human-induced pollution can alter breeding phenology and reproductive success in natural ecosystems. Long-term studies on monitoring reproductive performance in a highly polluted area are important to measure the environmental quality of a particular area. Harjavalta copper smelter is a significant point source of pollution in southwest Finland, which emits copper, nickel, lead, cadmium, arsenic, mercury, zinc, as well as sulphur dioxide to the surrounding environment. In this study, we investigated the probability of double brooding in great tit (Parus major) along a pre-determined pollution gradient surrounding the smelter to identify factors that affect the decision to start a second breeding attempt. The pollution gradient was categorized into two parts according to the distance from the copper smelter (polluted zone <2.5km and control zone >2.5-15km). These areas further included multiple nest box sites, and data were collected up to the site level for 33 years. Generalized linear mixed models were used to analyse the data. Population density was the major significant factor and negatively associated with the probability of double brooding, followed by the timing of breeding (first egg laying date of the 1st brood), whereas probability between polluted and control zones was not statistically significant. However, a positive relationship between first brood success (measured with the number of fledglings) and the likelihood of having a second brood was observed. The second brood probability showed a slightly negative trend over the study period. Contrary to some other life-history parameters documented in earlier studies, there was no significant impact of distance zone, suggesting that pollution is not an influential factor on the probability of multiple brooding.This study provides insights into density-dependent reproductive decisions and performance of great tits and suggests that higher local competition for resources is one of the major factors shaping the life-history decisions of great tits.
Keywords: Parus major, second broods, environmental pollution, timing of breeding, reproduction strategies